Single Parent Households and the Effect on Student Learning - Watt, Asia (2019)
The purpose of this research is to examine if there is a relationship between single-parent households and the effect on student learning. A total of seven parents and three elementary teachers took a survey. Students’ scores in math and reading from report cards and PARCC scores were also used as data sources. Results revealed that the involvement of single parents at school varies depending on the type of involvement, however, data from the report card review showed all the parents review their child’s report card. Approximately 70 % or more assisted their children in math and English homework. In addition, Pearson correlation reported that there were strong correlations between single parents and reviewing student report cards, r =.75, p .05, as well as attending field trips and review report card, r =.78, p .05. However, there is a weak relationship between parents who attended an open house and those who attended field trips, r =.00, p .05